NATIONAL BIBLIOGRAPHIES AND NATIONAL BIBLIOGRAPHIC METADATA IN THE AGE OF MASS INFORMATION [PRESENTATION] - Koskas, Mathilde (Nazarbayev University Library, 2021)
A presentation of the Bibliography section of IFLA : scope, activities, role in promoting National Bibliographies and national bibliographic metadata in this era of mass online information. National Bibliographies, as comprehensive, standardized, authoritative sources of information about the intellectual and cultural output of a country, have an important role to play today. This paper will outline the tools that the Bibliography section of IFLA makes available to agencies that wish to build or maintain strong National Bibliographies, that can contribute to access, selection and assessment of information.
Keywords: Type of access: Open Access; EALC